Interactive methods of teaching children and its theoretical basis - Alikulova, Karomat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
At present, a number of developed countries have accumulated rich experience in the use of pedagogical technologies that increase thelearning and creative activity of students and ensure the effectiveness of the educational process. is of particular importance.In this rapidly changing world, teachers' pedagogical skills, methods and techniques are changing, evolving and modernizing